Analyses of the development of education and science in Dnipropetrovsk region (descriptive-analytical context of the regional sustainable development strategy) - Matveieva O. (Theory and Practice of Public Administration, 2019)
The paper analyses the development of the education and science in Dnipropetrovsk region in the context of the pressing social, economic challenges and prospects of European integration of Ukraine.The purpose of this article is to study mainstream and trends in the field of education and science in the Dnipropetrovsk region during the period from 2014 to 2018. The level of secondary, vocational and higher education is considered, the key issues and development barriers are defined. The effect of destabilizing factors is analyzed. It is founded that the situation in this field was characterized by the following general tendencies: significant reduction in the financial support, systemic destabilization; decrease in the total number of consumers of educational services; reduction of qualitative indicators of education at all levels.The article provides proposals on prospective stabilization and enhancing the efficiency of management in the sphere of education and science regulation. Taking into account these trends, the important prospects of the crisis consequences overcoming in the educational and scientific system are as follows:− Increasing the prestige of work in the system of education and science, formation its positive image through social and organizational factors providing (modern social, medical provision, employment guarantees, especially the first place of work, development of a competitive-oriented personnel management system and their competency-age rotation for institutions of education and science), as well as economic incentives for expanding knowledge and deepening professional competences.− Comprehensive support for improving the quality of education and research: in education – through globalization and adaptation, the use of advanced approaches and educational systems in educational practice; in science – by integrating institutions into the European educational space and targeting the end-users of a scientific product.− Ensuring the economical and human-centric flexibility of the educational process on a competent basis, which corresponds to the tasks of forming an innovative globalized economy.−  Implementation of systematic monitoring and evaluation of the quality of education and research through surveys, as well as participation in international comparative studies on the success of students and students, and encouraging institutions to enter global ratings. This will contribute to the integration of regional education and science into European and world space.−  Diversification of financial support sources.Systemic following these priorities in the development of the field of education and science, as well as in the scientific-oriented modernization of the regional economic system, where it should be fully integrated, will provide a qualitatively new impetus to the development of the industry, increase the efficiency of services, competitiveness of institutions, which will significantly accelerate the European integration of Ukraine.